Learning Needs and Quality Care Among Family Caregivers and Elderly Patients of Guadalupe, Cebu City, Central Philippines - Alvarez, Ivan Cliff Chan; Ong, Marylou B.; Abocejo, Ferdinand T. (European Scientific Journal, ESJ, 2017)
This study assessed the learning needs of the family caregivers based on knowledge, skills, attitude and values (KSAV), their quality of care services and the elderly patients’ assessment on the quality of the provided care. The study utilised a descriptive-normative method employing survey research design utilizing a randomized cluster sampling technique. Primary data were collected using a standardised modified interview guide. Face-toface interviews were carried out to family caregivers and elderly patients in Guadalupe Village, Cebu City, Central Philippines. Findings revealed that caregiving jobs are mostly handled by women. Likewise, there were more female than male elderly patients, almost three-fourths of them attained high school or lower level education. Family caregivers’ possessed very good attitude and values. They were also good in terms of knowledge and skills toward the care of elderly patients. Similarly, elderly patients view their caregivers to be very good in attitude and values and good in terms of knowledge and skills. In conclusion, the learning needs among family care givers dealt more on understanding the nature, medical conditions, medication administration, caregiving techniques, diet and nutrition, ambulation techniques and strategies, financial supports from peers and total care management of the elderly patients. The provision of these learning needs anchored on the knowledge, skills, attitude and values ensures the caregivers from experiencing depressions, desperations, and self-isolation.